Do ecological and silvicultural factors influence acorn mass in Holm Oak (southwestern Spain)? - Alejano, R.; Vázquez-Piqué, J.; Carevic, F.; Fernández, M. (Agroforestry Systems, 2011)
The effect of orientation, location, year, and pruning treatment on mean acorn mass in two open woodland experimental locations (Huelva, South-Western Spain) of Holm Oak (Quercus ilex L. subsp. ballota [Desf.] Samp.) was analyzed during 2001–2006. Data were analyzed by using a mixed linear model, where the covariates were tree size parameters (circumference at 80 cm height, crown size), topographic position (wet index and ﬂow length), intraspeciﬁc competition, total acorn crops per tree (weight and number), and climatic parameters. Average estimated acorn mass was 3.17 g acorn -1 in the Calan˜as location and 4.12 g acorn -1 in the San Bartolome´ location, with signiﬁcant differences between locations, among individual trees and across years. Acorns from the south sides of trees were signiﬁcantly heavier than those at other positions. The effect of pruning treatment and the interactions location 9 treatment and treatment 9 year were not signiﬁcant. Our study provides no evidence that pruning affects acorn mass. None of the analyzed covariates related to tree size, topographic position and intraspeciﬁc competition explained the difference among trees, suggesting that heritable factors play an important role. Speciﬁc climatic parameters during September, the most important month for acorn growth, may explain the effects of year and location 9 year on acorn mass. In addition, there appeared to be a ‘‘trade-off’’ between acorn mass and number of acorns.
Keywords: acorn production; Dehesa; Quercus ilex